2023
DOI: 10.1021/acsomega.3c00441
|View full text |Cite
|
Sign up to set email alerts
|

Design and Computational Analysis of an MMP9 Inhibitor in Hypoxia-Induced Glioblastoma Multiforme

Abstract: The main therapeutic difficulties in treating hypoxia-induced glioblastoma multiforme (GBM) are toxicity of current treatments and the resistance brought on by the microenvironment. More effective therapeutic alternatives are urgently needed to reduce tumor lethality. Hence, we screened plant-based natural product panels intending to identify novel drugs without elevating drug resistance. We explored GEO for the hypoxia GBM model and compared hypoxic genes to non-neoplastic brain cells. A total of 2429 differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 116 publications
0
4
0
Order By: Relevance
“…Glioblastoma is the most common type of cancerous brain tumor in adults and it is usually fatal because of its severe and spreading behavior (48). MMP9 had a high level of expression in various kinds of GBM such as classical, mesenchymal tissue, neural, and proneural (49). New research has revealed that the circRNA made from MMP9 boosts the formation of tumors not only in glioblastoma but also in other cancerous cells (12).…”
Section: Discussionmentioning
confidence: 99%
“…Glioblastoma is the most common type of cancerous brain tumor in adults and it is usually fatal because of its severe and spreading behavior (48). MMP9 had a high level of expression in various kinds of GBM such as classical, mesenchymal tissue, neural, and proneural (49). New research has revealed that the circRNA made from MMP9 boosts the formation of tumors not only in glioblastoma but also in other cancerous cells (12).…”
Section: Discussionmentioning
confidence: 99%
“…Further, the obtained list of pathways of HBV-induced hepatitis was matched with pathways collected from “KEGG ID: hsa05161” and finalized with the matched pathways for HBV-modulated pathways for further analysis. In a similar manner, the list of pathways for chemically induced hepatitis and the HBV pathways were compared for similarity based on gene counts and false discovery rate (FDR) [ 262 , 263 ].…”
Section: Methodsmentioning
confidence: 99%
“…The output of the docking process included *.pdbqt files containing the top ten poses and *.txt files containing the binding affinity information of the top five poses from the docking results. The results were visualized using the PyMol [83] and LigPlot programs [84].…”
Section: Molecular Dockingmentioning
confidence: 99%